The Sehat dan Bahagia (SETIA): Optimalisasi dalam Meningkatkan Kesehatan Reproduksi pada Perempuan Menghadapi Menopause: Sehat dan Bahagia (SETIA): Optimalisasi dalam Meningkatkan Kesehatan Reproduksi pada Perempuan dalam Menghadapi Menopause - Rahmawati, Veronica Yeni; Puspasari, Jehan; Fitria, Dian; Sari, Andini Cahya Roslita; Ismoyo, Bayu (Idea Pengabdian Masyarakat, 2023)
Abstract: Women when entering the age of aging or approaching menopause often experience physical and psychological symptoms that can cause disruption of daily activities. Often women at the age of menopause feel themselves old, judge and think themselves sluggish and feel insignificant, causing stress to women. Adverse effects or severe symptoms of menopause can cause osteoporosis, heart disease, urinary incontinence and other health problems. The purpose of this activity is to increase the knowledge and insight of women in general to maintain menopausal reproductive health. The method of this activity is divided into several steps, starting with the socialization of the activity agenda, providing educational materials to women through face-to-face meetings, demonstrations of facial and muscle-relaxing exercises and finally an evaluation of menopause reproductive health knowledge. The result of this activity is an increase in knowledge of reproductive health in women before and after attending education. The provision of education packaged with demonstrations of gymnastic movements has proven to be effective in increasing women's knowledge about menopausal reproductive health.